PENGEMBANGAN KARAKTER PESERTA DIDIK MELALUI KEGIATAN KEPRAMUKAAN - Retno Triningsih (LPPM Universitas Pahlawan Tuanku Tambusai, 2019)
This study describes the development of character education through scouting activities. The purpose of this study is to find out about how to realize character education in schools, forms of scouting activities that can realize character education, and form the results of character education through scouting activities. The research method used is a qualitative method by using thought analysis by reference to various journals and books that have appeared before. The results of writing indicate that character building through scouting activities is carried out through the role of scout coaches as partners or mentors, providing support and facilitating students with activities that are modern, interesting, and challenging. The methods include: applying the scout honor code on each activity; learning activities while doing, grouping, working together, and competing; outdoor activities such as camps; awards in the form of skill marks, as well as separate units for male and female shelter. The writing results show that scouting activities can develop students' character to be better and can be a role model in the community in daily life by practicing and carrying out Tri Satya and Dasa Dharma as a reference to the young generation of the Indonesian nation with the Pancasila foundation.